Kontrol Lensa Pelanggan Re-Branding: Kontrol Konstruksi Real-time yang Dipersonalisasi, Proaktif, Bertujuan, dan Penuh Warna - Hefri Yodiansyah; Hari Jummaulana (CV Insan Kreasi Media, 2022)
This paper presents an analysis of the Expanded Public Works Program (EPWP), one of the ‘Driven Controls’ Re-Branding Customer key policy initiatives intended to ease the burden of poverty or unemployment on the poor and unskilled. Historically, such programs have been used as assistance during short-term crises. Lately, many ‘Driven Controls’ Customers have adopted it for long-term structural challenges. This program study in the G-20 government is intended to protect women and youth. This paper uses a mixed methodological approach to determine the active participation of women and youth in EPWP and their opportunities to transition to the labour marketplaces. This study also solicits the views of EPWP participants (see also, active and former) and officials to obtain information that is not included in the program's official report. Analytical procedures involve document analysis, focusing on EPWP reports from phases One (1) to Three (3) of the programs. This study proposes two propositions: the need for public-private partnerships to address the challenges of unemployment in the country because independent policies for the government or marketplace are inadequate; new program design that separates job seekers from social protection beneficiaries. In its current form, the EPWP is designed as a grassroots poverty trap.